An Investigation of the Thermophilic Bioleaching of Pyrite - G. E. Searby; G. S. Hansford (International Mineral Processing Congress, 2003)
The rate of bioleaching of pyrite at 70ºC by a thermophilic archaeal culture was measured as a function of the solution redox potential by the staged addition of pyrite to a batch system. The results were compared to the rate of ferrous iron oxidation over the same potential range to determine the applicability of the multi-sub-process leaching mechanism developed for mesophilic bioleach systems.